Classroom Symbols and the Ritual Dimensions of Schooling - McLaren, Peter L. (Anthropologica, 2022)
A great deal of conceptual confusion still surrounds the meaning of ritual. Consequently, the word "ritual" continues to have an ambiguous status in social science research. This is especially true of studies which attempt to analyze modern institutional life and contemporary cultural formations. This paper critically reexamines and reconsiders the term ritual in order to develop a conceptual model for the investigation of school instruction. Drawing upon recent advances in ritual studies, a "soft" definition of ritual is operational i zed during fieldwork in a Catholic middle school in downtown Toronto, Canada. A number of dominant states of interaction are identified which are analytically linked to a typology of ritual forms. Special emphasis is placed on the pedagogical manipulation of symbols.